AB0450 Effect of adalimumab discontinuation on patient-reported outcomes and work productivity in early rheumatoid arthritis patients who achieved low disease activity following 26 weeks of treatment: Data from the optima study. (23rd January 2014) - Kavanaugh, A.; Emery, P.; van Vollenhoven, R.; Cifaldi, M.; Shaw, J.; Chen, N.; Smolen, J.
Abstract : Background: Increasing attention has been focused on patient-reported outcomes (PROs) and work productivity as important outcomes in RA. In the O ptimal P rotocol for T reatment I nitiation with M ethotrexate (MTX) and A dalimumab (ADA) (OPTIMA) trial, results at 26 weeks (wks) showed a significant advantage of treatment with ADA vs. placebo (PBO) for achieving improved PROs. Objectives: To evaluate the impact of ADA discontinuation on PROs and work productivity, and variation in these outcomes with maintenance of low disease activity (LDA), in early RA patients who achieved LDA following 26 wks of ADA+MTX therapy. Methods: Patients were randomized to ADA+MTX (N=515) or PBO+MTX (N=517) for 26 wks. Those who achieved stable LDA (DAS28CRP <3.2) at wks 22 & 26 were re-randomized to ADA+MTX or PBO+MTX for an additional 52 wks. Patients completed the Work Productivity and Activity Impairment (WPAI) questionnaire, Work Instability Scale (WIS), Health Assessment Questionnaire (HAQ), and the Patient Acceptable Symptom State (PASS) classifier at baseline and subsequent time points. Treatment group differences in PROs were modeled assuming equality at time of re-randomization. All missing data were imputed using last observation carried forward. Results: Of 466 patients who completed 26 wks of ADA+MTX treatment, 207 (44.4%) achieved LDA at wks 22 and 26. Of these, 102 (49.3%) were assigned to discontinue ADA treatment (Arm 1), whilst 105 (50.7%) were assigned to continue treatment (Arm 2). There were no significant PRO differences between Arms 1 and 2 at the time of re-randomization. Compared with Arm 1, Arm 2 patients exhibited a lower mean WIS score (P=.004) and lower mean HAQ Disability Index (HAQ-DI) score (P=.012) at wk 52 as well as a lower mean WPAI Activity Impairment (WPAI-AI) score (P=.049) and superior level of PASS response (P=.045) at wk 66. PRO differences at wk 78 (end of study) were statistically insignificant. More patients in Arm 2 maintained LDA (91%) than did patients in Arm 1 (81%). In the combined group consisting of Arms 1 and 2, patients with sustained LDA between wks 26 and 78 maintained or improved work productivity and PROs, whilst those who did not sustain LDA worsened with respect to these outcomes (Table). Conclusions: Patients with sustained LDA maintain or improve upon work productivity and PRO gains, whilst those with increased disease activity deteriorate over time. Continued ADA+MTX treatment yields some benefits with respect to work productivity and PROs for patients who achieve LDA following 26 wks of ADA+MTX treatment. Disclosure of Interest: A. Kavanaugh Grant/Research support from: Abbott, Consultant for: Abbott, P. Emery Consultant for: Abbott, R. van Vollenhoven Grant/Research support from: Abbott, Consultant for: Abbott, M. Cifaldi Shareholder of: Abbott, Employee of: Abbott, J. Shaw Shareholder of: Abbott, Employee of: Abbott, N. Chen Shareholder of: Abbott, Employee of: Abbott, J. Smolen Grant/Research support from: Abbott, Consultant for: Abbott